PERILAKU SEKSUAL PRANIKAH MAHASISWA PADA SALAH SATU UNIVERSITAS DI KABUPATEN SUMBAWA - Aggasi, Abbyzar (Jurnal TAMBORA, 2020)
This study wanted to find out more about the premarital sexual behavior of students at one of the universities in Sumbawa Regency and their handling efforts. This research is based on the rise of premarital sex cases by students that occurred at one University in Sumbawa Regency (interview with Bunga, one of the students). This becomes interesting because the University is a campus with a very thick religious nuances both among Lecturers and Students. The University's location in "remote" villages in the Sumbawa Regency and far from the hustle and bustle of big cities with all kinds of "glamor" makes the University can be said to be a "clean" campus of hedonism activities. However, premarital sexual behavior can still be found and become a conversation among students and some lecturers at the University. This study uses two quantitative and qualitative methods which are compared to make this research more extensive and in-depth. Quantitatively this study wants to find out how much the involvement of students in one University in Sumbawa Regency in sexual behavior outside of marriage and qualitatively want to know the causes. The tool used was a survey and in-depth interviews of the students concerned at the University with a random purposive sampling method where respondents or informants were selected in accordance with research criteria to obtain the desired information. The objects in this study were students in the age range of 17-25 years. At this age students are still in the juvenile category (MOH, 2018). This research will produce outcomes in the form of Be-ISSN National scientific journal publications, and posters.